Autonomous Underwater Vehicle untuk Survei dan Pemantauan Laut - Henry M. Manik; Agung D. Syakti; Jales Veva Jaya; Dony Apdillah; Steven Solikin; Angga Dwinovantyo; Rina Fajaryanti; Bagas O. Siahaan; Muhammad Sanubari (Jurnal Rekayasa Elektrika, 2017)
AUV is an unmanned submersible platform to accomplish a mission. Side-scan sonar, Conductivity Temperature Depth (CTD), and underwater video camera are usually attached on AUV. These sensors were used for identifying seawater and seabed condition. Data acquired from a survey with an AUV in Kepulauan Riau processed by Neptus software. Side-scan sonar (SSS) visualization is compared to the video image. SSS signal visualization has a unique pattern that can be identified within the video image. Different substrate structure caused different signal visualization.  The relation between the video image and SSS visualization can be used for identifying habitat benthic profile.